DEVELOPMENT OF FUNDAMENTALS OF PERSONAL PHYSICAL CULTURE IN PRESCHOOL EDUCATION - Gafforova Mavjuda Mengdobilovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, the main principles and principles of the continuity of physical education are discussed in terms of the formation and improvement of the culture of health and healthy life using the means and methods of physical culture in a broad sense.